Shape Oscillation of a Single Microbubble in an Ultrasound Field. (15th August 2018) - Li, Xian; Bao, Fubing; Wang, Yuebing
Abstract : The shape oscillation of a single two-dimensional nitrogen microbubble in an ultrasound field is numerically investigated. The Navier–Stokes equations are solved by using the finite-volume method combined with the volume-of-fluid model. The numerical results are in good accordance with experimental and theoretical results reported. According to the analyses of the shape oscillation process, the bubble deformation period is twice the driving acoustic pressure period and the shape oscillation is mainly caused by the change of interface velocity. The vortexes produced due to velocity variations lead to the deformation of the bubble interface.